PENGARUH TEKNIK QUICK ON THE DRAW DISERTAI DENGAN PEMBERIAN HANDOUT TERHADAP HASIL BELAJAR SISWA KELAS VIII DI MTsN TARUSAN PESISIR SELATAN - Pebrika, Pebrika; Sudirman, Sudirman; Nerita, S.Pd, M.Pd, Siska (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ Â Teacher-centered learning (teacher center) is less attractive to some students resulting in low student learning outcomes obtained . The low yield is due to students learning tends to be passive during learning , the lack of interaction between students and teachers , and students with other students . Therefore, this study used the technique in the form of discussion which is a technique Quick On The Draw is accompanied by a handout that can make students more active and the interaction between students and other students or between students and teachers . This study aimed to examine the effect of quick on the draw techniques coupled with giving handouts on learning outcomes biology MTsN Tarusan eighth grade students on the material in the Human Respiratory System. This research is an experimental study with aÂ randomized study design posttest Only Control Group Design . Implementation research is conducted in an experimental class VIII.B class with 41 students and the number of classes that control VIII.C classes totaling40 students . Statistical hypothesis testing is used is the t-test . The results showed that the class that uses learning techniques Quick On The Draw has an average value of 80.07 is higher than the conventional classroom learning with the use of an average of 72.98. T-test results of testing on the real level of 0.05 obtained T count = 2.57 and T table = 1.66 means T count > T table . The conclusion of this research is the student learning outcomes obtained using learning techniques Quick On The Draw is accompanied by a handout higher than on student learning outcomes using conventional learning material on the human respiratory system in class VIII MTsN Tarusan South Coast.